Three Lectures on the Walrasian Hypotheses for Exchange Economies - Donald J. Brown (Yale University, Economic Growth Center, 1997)
This paper discusses the testable implications of the Walrasian hypotheses: H1 Observed market demand is the sum of consumer's demands derived from utility maximization subject to budget constraints. H2 There exists an observable (locally) unique equilibrium price system such that the observable market demand is equal to the observable market supply in every market. H3 The observed equilibrium price system is a (locally) stable equilibrium of ttonnement price adjustment. The main results are the Brown Matzkin Theorem: H1 is testable, and the Brown Shannon Theorem: H2 and H3 are not testable.
Keywords: 330; Exchange Economies; Testable Restrictions; Tauschwirtschaft; Allgemeines Gleichgewicht; Theorie